(untitled) (Bangladesh Journal of Medicine, 2025)
Dengue virus, an RNA virus linked to a wide range of neurological symptoms, causes less than 5% of patients to experience neuromuscular complications. A less frequent neurological sequelae to dengue fever is Guillain-Barre syndrome (GBS). Six days after recovering from dengue fever, a 25-year-old woman with the illness presented with acute-onset flaccid paraplegia of both lower limbs. Dengue NS1 antigen testing was used to diagnose dengue. In the NCS test, an acute motor axonal neuropathy (AMAN) variant was found. Thrombocytopenia (36,000/cmm), hypoalbuminemia (2.30 g/dL), and a low hemoglobin level (Hb-10.3 gm/dL) were among the laboratory results, which most likely indicated post-dengue symptoms and nutritional inadequacies. The significance of early neurophysiological and CSF tests in detecting GBS variations is highlighted by this instance, which also identifies dengue as an AMAN variant. Bangladesh J Medicine 2025; 36(2): 149-153